LONDON in Bloom - Lane, Georgianna; Dozier, Laura (New York : Abrams Image, 2020)
London in Bloom showcases the floral abundance of the English capital's extraordinary parks, gardens, florists, and flower markets. In this companion to her popular books Paris in Bloom and New York in Bloom, Georgianna Lane takes us on a romantic floral tour of London, juxtaposing luscious blooms with intricate floral details found in the city's iconic architecture. The book also includes a detailed list of recommended parks, gardens, markets, and floral designers; a spring tour of blossoms and blooms; a field guide of common spring-blooming trees and shrubs; and step-by-step instructions for creating a London-style bouquet. For flower lovers and Anglophiles alike, London in Bloom offers a unique and irresistible view of London.
t t Floral displays.
Includes index of photographs.
Keywords: Lane, Georgianna; Photography of plants -- England -- London; Street photography -- England -- London; Documentary photographs; Creative nonfiction; Pictorial works